SAS from World War II to the Gulf War - Darman, Peter (Amber Books, 2019)
From spectacular hostage-rescue operations in the heart of London to covert counterterrorist missions in Northern Ireland, the soldiers of the Special Air Service (SAS) Regiment are second to none. With the aid of more than 600 alphabetically arranged entries, SAS: From WWII to the Gulf War offers an in-depth analysis of every aspect of the unit's 50-year history. It lists all the Regiment's battles and campaigns, together with their economic, political, and strategic background, and the weapons, equipment, and techniques they use. Biographies cover all the leading personalities who have worn the famous winged dagger badge, including "Paddy" Mayne, David Stirling, the Regiment's founder, and Sir Peter de la Billière, who commanded British forces during the First Gulf War.